Benign Infantile Convulsions with Gastroenteritis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The clinical features of benign convulsions with mild gastroenteritis (CwG) were studied retrospectively in 62 patients hospitalized (Jan 2000-March 2006) at St Mary's Hospital, Kurume City, Japan.